The Influence of Family Factors on Smoking Behavior in Turkey - Oncel, Sevgi Yurt; Aliev, Fazil (International Journal of Statistics in Medical Research, 2014)
Aim: The goal of this study is to specify the risks, family and environmental factors affecting smoking behavior and develop suggestions for Turkish individuals by considering sibling data. Materials and Methods: The data was collected by voluntary senior year students attending Kırıkkale University, Department of Statistics. The sample of 751 families was selected from families with at least two children. Each sibling’s socio-demographic information and behavioral phenotypes were collected using a survey from both siblings. We selected one of siblings randomly as ‘sibling1’ and defined the other sibling as ‘sibling2’. Hypothesis testing and multivariable clustered logistic regression models were used to evaluate the data and find the optimum model by using dependent sibling data. Results: Out of 1502 (751 pairs) siblings 843 (56.1%) were males, 659 (43.9%) were females. According to the survey results, 508 of the males (67.7%) and 242 of the females (32.3%) were smokers for a month or longer and smoked every day. The risk of smoking was 2.26 times higher in males than in females. Having a smoking sibling increased the risk of smoking 1.95 times, alcohol using increased the risk 2.11 times. We found that when the age difference between siblings is 0-7 years, having a same sex sibling who smokes increases one’s risk 4.7 times in females and 5 times in males; when the siblings are of different sexes, according to these age differences Conclusion: The survey showed that the gender and sibling’s and parent’s smoking both play a significant role on smoking behavior. But children seem to learn smoking from their siblings more than from parents. Having same sex sibling who smokes plays significant role in smoking behavior for both males and females.